Regulation Of Lifestyle Diseases Through Yoga Practice - kumari, Babita; Verma, Monika; Mishra, Pramood Kumar; Kumar, Mahesh (International Research Journal of Ayurveda & Yoga, 2021)
A disease is particular abnormal pathological conditions. That effects part of all of an organism or pathological conditions of a part, organs or systems of an organism resulting from various causes, such as infections, genetic, defects, or environment stress and characterized by an identifiable group of sign or symptoms . Human life is more stressful in the present era. Lifestyle disorders are primarily resulted due to improper diet (mostly fat and sugar) and dietary patterns, lack of exercise (sedentary lifestyle),bad habits like alcohol, drinking, smoking, uncontrolled desires, late night sleep, day sleep, and psychosocial stress. Common life style disease included are communicable disease, hereditary disease, deficiency disease, heart disease, smoking, obesity, high blood pressure, coronary artery disease, bronchial asthma, diabetes mellitus, chronic liver disease, psoriasis, arthritis, cancer, and physical inactivity are more prevalent among SEP (socio economic positions) persons. Social inequalities in chronic disease morbidity and mortality will persist in the next decades (UN Report).Non communicable disease leading causes of death around the world, with developing countries hit fast, according to a new report from the WHO. The modern world is facing a pandemic of lifestyle disease that require change to be made consciously by individual themselves. The holistic art and science of yoga is the best lifestyle ever designed and effective, yoga provides great option for the preventions and management for lifestyle diseases, particularly, yoga has been found effective to manage work related stress. Different yoga practices works on the principles of proper relaxation, proper exercise, proper breathing, proper diet, positive thinking and meditation. Yoga based lifestyle involves life style modification based on the concepts of promotion of psychosomatic and spiritual health and proper living. This way yoga is found more effective for promotion of psychosomatic and spiritual health, prevention and management of life style diseases and rehabilitation as well